Long-term exposure to air pollution and COVID-19 severity: A cohort study in Greater Manchester, United Kingdom. (15th June 2023) - Hyman, Samuel; Zhang, Jiawei; Andersen, Zorana Jovanovic; Cruickshank, Sheena; Møller, Peter; Daras, Konstantinos; Williams, Richard; Topping, David; Lim, Youn-Hee
Abstract: Exposure to outdoor air pollution may affect incidence and severity of coronavirus disease 2019 (COVID-19). In this retrospective cohort based on patient records from the Greater Manchester Care Records, all first COVID-19 cases diagnosed between March 1, 2020 and May 31, 2022 were followed until COVID-19 related hospitalization or death within 28 days. Long-term exposure was estimated using mean annual concentrations of particulate matter with diameter ≤2.5 μm (PM2.5 ), ≤10 μm (PM10 ), nitrogen dioxide (NO2 ), ozone (O3 ), sulphur dioxide (SO2 ) and benzene (C6 H6 ) in 2019 using a validated air pollution model developed by the Department for Environment, Food and Rural Affairs (DEFRA). The association of long-term exposure to air pollution with COVID-19 hospitalization and mortality were estimated using multivariate logistic regression models after adjusting for potential individual, temporal and spatial confounders. Significant positive associations were observed between PM2.5, PM10, NO2, SO2, benzene and COVID-19 hospital admissions with odds ratios (95% Confidence Intervals [CI]) of 1.27 (1.25–1.30), 1.15 (1.13–1.17), 1.12 (1.10–1.14), 1.16 (1.14–1.18), and 1.39 (1.36–1.42), (per interquartile range [IQR]), respectively. Significant positive associations were also observed between PM2.5, PM10, SO2, or benzene and COVID-19 mortality with odds ratios (95% CI) of 1.39 (1.31–1.48), 1.23 (1.17–1.30), 1.18 (1.12–1.24), and 1.62 (1.52–1.72), per IQR, respectively. Individuals who were older, overweight or obese, current smokers, or had underlying comorbidities showed greater associations between all pollutants of interest and hospital admission, compared to the corresponding groups. Long-term exposure to air pollution is associated with developing severe COVID-19 after a positive SARS-CoV-2 infection, resulting in hospitalization or death. Graphical abstract: Image 1 Highlights: This is a retrospective cohort study covering an entire UK region (Greater Manchester). Long-term exposure to particulates was associated with COVID-19 severity. SO2 and benzene had stronger associations than NO2 to COVID-19 severity. Old, obese and smokers are most susceptible to air pollution-associated COVID-19.